2011
DOI: 10.1111/j.1365-3059.2010.02419.x
|View full text |Cite
|
Sign up to set email alerts
|

Development of a specific molecular tool for detecting Xanthomonas campestris pv. musacearum

Abstract: A specific and rapid diagnostic tool has been developed to detect Xanthomonas campestris pv. musacearum, the causal agent of bacterial wilt of banana. PCR primers were developed from intergenic regions of X. campestris pv. musacearum following its partial sequence. A total of 48 primers were tested for specificity to X. campestris pv. musacearum strains collected from various regions in Uganda. These were also tested for specificity against related Xanthomonas species from the vasicola group, Xanthomonas speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 30 publications
1
33
0
Order By: Relevance
“…However, this gene is also conserved in Xvv and this assay was unable to distinguish between Xcm and non-banana-pathogenic isolates Xvv NCPPB702 and NCPPB1326 [22]. Another study [23] generated several PCR primer pairs that were highly specific for Xcm but this study did not utilize Xcm or Xvv genomic sequence but rather used sequences from a range of other xanthomonads and so the candidate primers had to be tested for specificity by trial and error. Another recent study [24] exploited our previous [12] Xcm and Xvv draft genome sequence data to rationally design primers specific for Xcm .…”
Section: Resultsmentioning
confidence: 99%
“…However, this gene is also conserved in Xvv and this assay was unable to distinguish between Xcm and non-banana-pathogenic isolates Xvv NCPPB702 and NCPPB1326 [22]. Another study [23] generated several PCR primer pairs that were highly specific for Xcm but this study did not utilize Xcm or Xvv genomic sequence but rather used sequences from a range of other xanthomonads and so the candidate primers had to be tested for specificity by trial and error. Another recent study [24] exploited our previous [12] Xcm and Xvv draft genome sequence data to rationally design primers specific for Xcm .…”
Section: Resultsmentioning
confidence: 99%
“…Investigations into the sensitivity of the LAMP assay showed a limit of detection in the order of femtograms of target DNA. Comparison with the Xcm PCR assay of Adikini et al (2011), the equivalent laboratory-based molecular technique, revealed that the LAMP assay demonstrated greater levels of sensitivity by two orders of magnitude. Given that this PCR assay is stated as able to detect Xcm in nonsymptomatic plant material, it can therefore be inferred that the LAMP assay would successfully detect Xcm in asymptomatic plant material, along with its demonstrated ability to detect Xcm in symp-tomatic plant material.…”
Section: Discussionmentioning
confidence: 99%
“…These are primarily comprised of lab-based techniques, which are typically culturing or molecular approaches. Culture-based techniques include the use of semi-selective media (Mwangi et al 2007;Tripathi et al 2007) and biochemical profiling, while molecular-based techniques predominately use PCR, rep-PCR and RFLP (Versalovic et al 1994;Lewis Ivey et al 2010;Adikini et al 2011;Adriko et al 2012;Ferreira-Tonin et al 2012;Wasukira et al 2012). These techniques provide a range of specificities, and have associated advantages and disadvantages.…”
Section: Introductionmentioning
confidence: 99%
“…Data were collected on the percentage of diseased plants and incubation period in the inoculated mother plants and the attached lateral shoots. Possible latent infections were also assessed in 52 AAA-EA and 91 Pisang Awak symptomless suckers across all treatments 40 months after trial establishment, using PCR amplification of Xcm-specific DNA fragments (650 bp) using the Xcm-specific primer set Xcm38 (Adikini et al, 2011). Thirty uninoculated control plants of each cultivar were similarly tested to check for evidence of natural infection.…”
Section: Routes Of Infection In Banana Inflorescences Xw Incidence Amentioning
confidence: 99%